(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study investigates the impact of implementing ISO 31000 risk management standards on the effectiveness of risk management at Saudi petrochemical companies, a leading company in the petrochemical industry. ISO 31000 is a globally recognized framework that provides principles and guidelines for managing risks systematically and effectively. The study begins with an overview of the importance of risk management in large organizations, highlighting the challenges and risks faced by companies in a complex and dynamic environment. It then reviews ISO 31000 standards, including its core principles and framework aimed at improving the risk identification, assessment, and treatment processes. Additionally, the study examines the current risk management practices at Saudi petrochemical companies and evaluates how the application of ISO 31000 standards has influenced these practices. The research employs a methodology that includes collecting data through surveys and interviews with employees and risk management officials at the company, as well as analyzing relevant documents related to processes and policies. The findings indicate that the implementation of ISO 31000 has significantly enhanced the effectiveness of risk management at Saudi petrochemical companies. Notable benefits include improved risk identification and assessment accuracy, as well as the development of more effective risk treatment strategies. The standards also contributed to raising risk awareness within the company and fostering a more adaptive organizational culture capable of addressing new challenges. The study also identifies some challenges encountered during the application of the standards, such as the need for ongoing training and the development of advanced analytical tools. However, the benefits achieved outweigh these challenges, suggesting that investing in ISO 31000 implementation can be highly valuable for leading companies. Based on the results, the study recommends continuing to enhance the application of ISO 31000 across all departments within the company, developing regular training programs to ensure employee adherence to the standards, and further improving the tools and methods used in risk management to achieve optimal effectiveness. This study provides valuable insights into improving risk management in large organizations and offers practical models that other companies across various sectors can benefit from.